2017
DOI: 10.1111/jav.01464
|View full text |Cite
|
Sign up to set email alerts
|

A pre‐breeding immune challenge delays reproduction in the female dark‐eyed junco Junco hyemalis

Abstract: Precise timing of life‐history transitions in predictably changing environments is hypothesized to aid in individual survival and reproductive success, by appropriately matching an animal's physiology and behavior with prevailing environmental conditions. Therefore, it is imperative for individuals to time energetically costly life‐history stages (i.e. reproduction) so they overlap with seasonal peaks in food abundance and quality. Female lifetime reproductive fitness is affected by several factors that influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Such challenges could include enduring harsh early‐season environmental conditions such as inclement weather (e.g., Ramos et al 2002), low food availability (e.g., Young 1994, Bowlin and Winkler 2004), high levels of predation (e.g., Borgmann et al 2013), or competition for scarce nesting sites or mates (e.g., Smith 2006). Several studies of timing of breeding have explored the connection between quality and date experimentally (reviewed in Verhulst and Nilsson 2008) or by examining facets of fitness beyond reproduction (Brinkof et al 2002, Brown et al 2015, Low et al 2015, Needham et al 2017, Evans et al 2019). However, in the latter cases, breeding adults have usually been followed only to the season just after the focal breeding attempt.…”
Section: Introductionmentioning
confidence: 99%
“…Such challenges could include enduring harsh early‐season environmental conditions such as inclement weather (e.g., Ramos et al 2002), low food availability (e.g., Young 1994, Bowlin and Winkler 2004), high levels of predation (e.g., Borgmann et al 2013), or competition for scarce nesting sites or mates (e.g., Smith 2006). Several studies of timing of breeding have explored the connection between quality and date experimentally (reviewed in Verhulst and Nilsson 2008) or by examining facets of fitness beyond reproduction (Brinkof et al 2002, Brown et al 2015, Low et al 2015, Needham et al 2017, Evans et al 2019). However, in the latter cases, breeding adults have usually been followed only to the season just after the focal breeding attempt.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic supplementary material The online version of this article (https://doi.org/10.1007/s10211-020-00351-w) contains supplementary material, which is available to authorized users. Some of the avian studies that employed immune challenge showed its negative influence on clutch initiation date, egg size, brood size, brood feeding rates, chick quality, reproductive success and time to relay a replacement clutch (Ilmonen et al 2000;Råberg et al 2000;Bonneaud et al 2003;Marzal et al 2007;Gasparini et al 2009;Cucco et al 2010;Needham et al 2017). These results lend support for the costly immunity hypothesis, stating that costs of mounting an immune response are negatively reflected in current reproduction.…”
Section: Introductionmentioning
confidence: 89%